What can myxomycetes tell us about floricolous microbial systems? - Rojas Alvarado, Carlos Alonso (2017)
The study described herein was conducted in Costa Rica in an effort to generate baseline data on the association between tropical inflorescences and a group of microorganisms known as myxomycetes. The assemblage structure of myxomycetes was tested in three canopy cover classes between two independent study areas subject to different management strategies. One study area was an isolated patch in a suburban location while the other was located in a protected area with extensive connectivity to several national parks. Twenty-four species were recorded with only small differences in species occurrence and diversity between the two study areas. However, differences in diversity estimators were found for assemblages among the canopy cover classes within each study area. Intermediate and open canopy cover classes were the most dissimilar for the complete investigation, with those in the area with high forest connectivity and lack of plant manipulation being the ones responsible for the majority of the differences. Differences in assemblage structure among canopy cover categories were associated with differences in pH values. This study found a strong connection between monocot plants and myxomycetes in tropical environments and provides additional evidence for the existence of a guild of floricolous myxomycetes. The results suggest that vector-driven colonization of inflorescences by myxomycetes may be partially responsible for their occurrence in this microhabitat, but additional studies are required. Our study showed a resilient system of interaction that would naturally occur in different environmental conditions, suggesting a strong and stable relationship.